Pesticides Registered for Tropical Fruit Crops in Florida - Jonathan H. Crane; Mark A. Mossler (EDIS)
Tables of pesticides registered for use in Florida on the following tropical fruit crops: Atemoya and sugar apple; Avocado; Banana and plantain; Barbados cherry; Black sapote;  Carambola;  Coconut;  Guava;  Jackfruit; 'Tahiti' lime, Key lime, kumquat, and pummelo; Lychee and longan; Mamey sapote; Mango; Papaya; Passion fruit; Sapodilla; Wax jambu; and White sapote.